Voter Participation and Electoral Integrity in Nigeria’s 2019 General Elections - Omilusi, Mike; Gbenga, Olorunfemi (Advances in Social Sciences Research Journal, 2021)
This paper examines the inclusivity and legitimacy of elections in Nigeria’s Fourth Republic amidst, concerns continually expressed over the zero-sum nature of Nigerian politics, which manifests in the rising tide of contentious elections. Issues such as logistical failures and delays, misconduct and irregularities, violence, challenges of internal party democracy, corruption and a biased judiciary, have almost become permanent features of electioneering in the country. The paper explores the value mechanisms and processes that can enable an electoral process that guarantees transparency and accountability based on Nigeria’s electoral laws and regional instruments, such as the African Charter on Human and Peoples’ Rights, provides a credible opportunity for broad based participation, enables significant roles for the judiciary, anticorruption bodies, civil society organisations, and political parties as well as provide the strategic tools to ensure the credibility and integrity of each stage of the electoral cycle. The context of the 2019 elections, which recorded the participation of only a third of the 84 million eligible voters, will provide a barometer to measure the overall health of Nigeria’s electoral democracy, drawing extensively from secondary sources.